Comparison of nutritional, bioactive potential and antioxidant properties of Saba senegalensis fruit pulps from five regions of Burkina Faso - Tiendrebeogo, Salamata; Compaoré, Clarisse Sidbewendé; Barry, Raymond Poussian; Oboulbiga, Edwige Bahanla; Hama Dicko, Mamoudou (Frontiers in Nutrition, 2024)
The fruit of Saba senegalensis plays an important role in household nutrition. It is an important source of sweet carbohydrates, minerals, vitamin C, provitamin A and has many biological properties. It is also of economical importance and employment for rural populations, through the processing of fruit. Unfortunately, the lack of exhaustive data on the composition and properties of the fruit and its derivatives limits processing and marketing. The species is widespread in different climatic zones. Therefore, its composition and biological properties may vary, offering a variety of processing products to meet the specific nutritional needs. This study aimed to characterize the bioactive potential and antioxidant properties of fruit pulps of S. senegalensis in order to increase its value-added processing. Pulp samples of fruits were sampled from five regions of Burkina Faso, namely the Cascades, Sud-Ouest, Boucle du Mouhoun, Nord and Centre-Sud regions. Qualitative analysis showed the presence of alkaloids, saponins, terpenoids and steroids, anthocyanins and tannins. Quantitative analyses showed a significant variation in phenolics, tannins, lycopene, vitamin C, β-carotene and antioxidant activity among samples. However, this variation was not region-dependent. Indeed, some fruits from same region showed both the highest and lowest values for the assessed parameters. Fruits from regions of Centre-Sud and Sud-Ouest and displayed the highest and lowest levels of total phenolics (877.48 and 1142.33 mg GAE/100 g) and tannins (42.38 and 55.64 mg TAE/100g), respectively. The high potential of S. senegalensis fruits pulp in nutritional and bioactive compounds, and antioxidant properties recorded in this study suggests that they can be used as a dietary supplement or in the formulation of energy foods and nutraceutical containing foods.